Multi-Parametric MR Imaging in Characterisation of Benign and Malignant PhyllodesTumours - Pratiksha Yadav; Vilasm Kulkarni; Surbhi Chauhan (International Journal of Anatomy Radiology and Surgery, 2019)
Introduction: Phyllodes tumours are rare tumours of the breast.They present as painless nodules with rapid growth. Mammography and Ultrasound breast cannot provide adequate evaluation when the size of the phyllodes tumours are very large. MRI is very useful and excellent modality for evaluation of size, extent, pectoralis muscle and chest wall involvement. It is very helpful to differentiate the benign and malignant phyllodes tumour. Aim: To characterize the phyllodes tumour on MR imaging and to evaluate the MRI findings in differentiating benign and malignant phyllodes. Materials and Methods: A retrospective descriptive study was conducted on histologically proven phyllodes tumour of the breast in which 23 patients were included. Multi-parametric MRI of breast was performed on 1.5 Tesla Siemen’s Avanto machine using dedicated breast coil. Pre contrast, post contrast dynamic MRI and DWI sequences were obtained. Post processing and kinetic curve analysis was done using mean curve technique. Histopathological reports were accepted as standard of reference. Results: Out of 23 phyllodes tumour, five were malignant (21.7%), 18 (78.2%) were benign phyllodes tumour. Multiple septations were seen in the 18 lesions (78.26%). Cystic areas are seen in the 15 lesions (65.21%).On post-contrast study, these lesions showed heterogeneous enhancement. An eleven (47.82) lesions showed type I kinetic curve, seven (30.43%) showed type II curve and five (21.73%) lesions showed type III kinetic curve. Three malignant and one benign lesion showed restriction on DWI with corresponding low ADC values. MR spectroscopy was done in five patients and in two malignant patients it showed choline peak, three benign lesions did not show choline peak on spectroscopy. Conclusion: MRI is an excellent non-invasive modality for the characterization and evaluation of the phyllodes tumour as they are very large many times and could not properly evaluate on mammography and USG breast.